Development of functional meat paste technology - A. A. Hayrapetyan (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2021)
Most scientists agree that combining meat and vegetable raw materials is the most promising way to solve the problem of healthy eating. The combination of raw materials allows you to obtain a variety of high-quality products, expands the range and allows you to enter the optimal customized recipes to ensure the best consistency and biological value of the finished product. The article discusses the development of a technology for obtaining a functional food product using meat and vegetable raw materials. The aim of the study is to develop a combined food product for therapeutic, prophylactic and functional purposes. An improved recipe for rabbit meat paste with the addition of plant components is proposed. The developed technology was used to produce meat pastes based on a balanced ratio of the main food ingredients, providing improved digestibility, assimilability, biological value while achieving the best consistency. Rabbit meat is used as a meat component. Chickpea flour, onions, garlic, sesame oil, carrots, table salt, cloves, ground black pepper, paprika, broth and water were used as plant components. The broth obtained after boiling the rabbit is used. Quality assessment by organoleptic and physicochemical parameters was carried out according to generally accepted methods. This recipe made it possible to obtain a food product of a functional orientation, balanced in chemical composition, containing vegetable and animal proteins, fats, a sufficient amount of carbohydrates, vitamins A, C, E and such biologically significant elements as iron, calcium, potassium, sodium, magnesium, phosphorus, manganese, zinc, iodine, etc., with high organoleptic characteristics. The mass fraction of protein was at least 16.5%, fat - 17.2%, carbohydrates - 1.5%. The calorie content of 100 g of finished paste was 226 Kcal.